Advancing knowledge of the plant nuclear periphery and its application for crop science. Issue 1 (1st January 2020) - Evans, David E.; Mermet, Sarah; Tatout, Christophe
ABSTRACT: In this review, we explore recent advances in knowledge of the structure and dynamics of the plant nuclear envelope. As a paradigm, we focused our attention on the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex, a structurally conserved bridging complex comprising SUN domain proteins in the inner nuclear membrane and KASH domain proteins in the outer nuclear membrane. Studies have revealed that this bridging complex has multiple functions with structural roles in positioning the nucleus within the cell, conveying signals across the membrane and organizing chromatin in the 3D nuclear space with impact on gene transcription. We also provide an up-to-date survey in nuclear dynamics research achieved so far in the model plant Arabidopsis thaliana that highlights its potential impact on several key plant functions such as growth, seed maturation and germination, reproduction and response to biotic and abiotic stress. Finally, we bring evidences that most of the constituents of the LINC Complex and associated components are, with some specificities, conserved in monocot and dicot crop species and are displaying very similar functions to those described for Arabidopsis . This leads us to suggest that a better knowledge of this system and a better account of its potential applications will in the future enhance the resilience and productivity of crop plants.